Controls of Employee Performance Appraisal under the Saudi Labor Law: An Analytical Study - Asmaa Jamil Abdulhamid Ali; Amal Shalabi Khadragey (International Journal of Law Research and Studies, 2026)
This analytical study aimed to contextualize the legal concept of employee performance appraisal under the Saudi Labor Law, examining the formal and substantive constraints governing the employer’s exercise of this authority. The research problem highlights the practical gap resulting from the absence of precise statutory standards, which allows performance reports to be leveraged arbitrarily to deprive workers of accrued rights or unlawfully terminate employment. The study primarily adopted an analytical methodology, supplemented by a descriptive approach where necessary, to examine relevant statutory texts and unified model bylaws. The study yielded several key findings: performance appraisal constitutes a practical exercise of legal subordination; and labor law strictly prohibits utilizing negative appraisals to unilaterally modify basic wages or fixed allowances. Furthermore, the study revealed the inefficiency of internal grievance mechanisms and amicable settlement procedures due to their lack of binding enforcement power, shifting a heavy burden onto the employee to prove the employer's hidden malicious intent before labor courts. The study recommended strengthening the supervisory oversight of the Ministry of Human Resources when approving internal bylaws, and issuing a unified guiding regulation defining mandatory procedural pathways and timeframes for improving low-performing employees' skills prior to contract termination.
Keywords: Discretionary Authority; Performance Appraisal; Saudi Labor Law; Abuse of Rights